2008
DOI: 10.1007/s11596-008-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-trans retinoic acid on liver fibrosis induced by common bile duct ligation in rats

Abstract: The aim of this study was to investigate the effect and possible mechanism of all-trans retinoic acid (ATRA) on liver fibrosis induced by common bile duct ligation (CBDL) in rats. Fifty-three female Wistar rats were randomly divided into 5 groups: sham operation group (group J, 5 animals) and groups A, B, C and D (12 animals in each group). The rats in groups A, B, C and D were subjected to CBDL to induce liver fibrosis, while those in group J to sham operation. From the 3rd week the rats in groups B, C and D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…ATRA inhibits TGF-β stimulation of pro-fibrotic molecules in cultured mesangial cells, including fibronectin and PAI-1 86 . Similarly, ATRA inhibits TGF-β-driven liver fibrosis in a rat common bile duct ligation model 87 . TGF-β increases vascular endothelial growth factor (VEGF) production by cultured smooth muscle cells 88 and endometrial cells; in the latter cells, this effect requires ATRA, which initiates a process whereby VEGF mRNA transcripts are directed toward larger, poly-ribosomes that are more translationally active 89 .…”
Section: Tissue Repair: Cytoprotection and Anti-fibrosismentioning
confidence: 98%
“…ATRA inhibits TGF-β stimulation of pro-fibrotic molecules in cultured mesangial cells, including fibronectin and PAI-1 86 . Similarly, ATRA inhibits TGF-β-driven liver fibrosis in a rat common bile duct ligation model 87 . TGF-β increases vascular endothelial growth factor (VEGF) production by cultured smooth muscle cells 88 and endometrial cells; in the latter cells, this effect requires ATRA, which initiates a process whereby VEGF mRNA transcripts are directed toward larger, poly-ribosomes that are more translationally active 89 .…”
Section: Tissue Repair: Cytoprotection and Anti-fibrosismentioning
confidence: 98%
“…Animals were randomly divided into five groups/six rats each: control saline group: rats were injected with saline (0.2 ml/100 g.bw, I.P) once daily for 10 days; control DMSO group: rats were injected with DMSO, the vehicle of all-trans retinoic acid (ATRA), (0.2 ml /200 g.bw/day, I.P) for 10 consecutive days. MTX group: rats were injected with MTX in a single dose of 20 mg/kg on the sixth day of the experiment; ATRA group: rats were injected with ATRA (7.5 mg/kg/day, I.P) for 10 consecutive days (Rao et al 2010;Wang et al 2008); ATRA/MTX group: rats were injected with ATRA (7.5 mg/kg/day, IP) for 10 consecutive days while a single dose of MTX (20 mg/kg) was injected on the sixth day of ATRA injection. On the 11th day, rats were anesthetized with diethyl ether and blood samples were collected for measurement of blood chemistry.…”
Section: Animal Modelmentioning
confidence: 99%
“…Equally, Yang KL et al [16] reported that a RA derivative isolated from the mycelium of Phellinus linteus could antagonize ECM accumulation and liver fibrosis in BALB/c mice by down-regulating reactive oxygen species (ROS) generation and calcium influx, thereby directly affecting transforming growth factor-β1 (TGF-β1). Wang H and co-workers [17] showed that ATRA (1.5 and 7.5 mg/kg) was able to inhibit common bile duct ligation (CBDL)-induced liver fibrosis in female Wistar rats, and ATRA reduced the expression of collagen I protein more greatly than that of 0.1 mg/kg. The expression of type I collagen (COL-I), tissue inhibitors of metalloproteinase-1 (TIMP-1), TGF-β1, and connective tissue growth factor (CTGF) were reduced, whilst He H et al [18] reported that 5 mg/kg ATRA significantly reduced liver fibrosis and nearly eliminated liver necrosis after CBDL in male Sprague-Dawley rats, especially in combination with ursodeoxycholic acid (UDCA).…”
Section: Role Of Ra In Diseasesmentioning
confidence: 99%